2012
DOI: 10.1093/icesjms/fsr181
|View full text |Cite
|
Sign up to set email alerts
|

Short-term choice behaviour in a mixed fishery: investigating métier selection in the Danish gillnet fishery

Abstract: Andersen, B. S., Ulrich, C., Eigaard, O. R., and Christensen, A-S. 2012. Short-term choice behaviour in a mixed fishery: investigating métier selection in the Danish gillnet fishery. – ICES Journal of Marine Science, 69: 131–143. The study presents a short-term effort allocation modelling approach based on a discrete choice random utility model combined with a survey questionnaire to examine the selection of métiers (a combination of fishing area and target species) in the Danish North Sea gillnet fishery. Key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 40 publications
3
29
0
3
Order By: Relevance
“…The fleet-based approaches make aggregated groups of similar activities to account for the heterogeneity of the fishing practices and profitability . Effort allocation models for the commercial fishery such as statistical random utility models (RUMs) are usually used on top of this approach and also perform at the aggregated fleet scale (e.g., Andersen et al 2012). RUMs can provide some probabilistic choices of fishing location and accordingly a realistic division of the overall fishing effort that accounts for local resource depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The fleet-based approaches make aggregated groups of similar activities to account for the heterogeneity of the fishing practices and profitability . Effort allocation models for the commercial fishery such as statistical random utility models (RUMs) are usually used on top of this approach and also perform at the aggregated fleet scale (e.g., Andersen et al 2012). RUMs can provide some probabilistic choices of fishing location and accordingly a realistic division of the overall fishing effort that accounts for local resource depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The local knowledge on the spatial-temporal migration dynamics of target species, the temporal variations in recent catches, the weather, the personal preferences of the skipper, the fish prices, the fishing regulations, and the gears they are allowed to use from their licence are some of the influential aspects in the selection of fishing strategy, and ultimately in the temporal pattern of the fishing activities (Andersen et al 2012). Thus, we have observed that strategies targeting sardine (Ce_1 and Xe_1) are mainly used in late spring and early summer, when the sardines approach the coast (Villasante 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The gillnet fleet is of importance in Denmark and is gaining interest as an alternative practice towards improved environmental sustainability with regard to energy use and ecosystem effects (Andersen, Ulrich, Eigaard, & Christensen, 2012;Suuronen et al, 2012). The coastal vessels provide the opportunity of daily fresh fish supply, but maintaining profitable is challenging, and calls for solutions to help improve catch production.…”
Section: Introductionmentioning
confidence: 99%